Toxoplasmose gestacional e congênita no município de Ponta Grossa: um estudo retrospectivo - Volanin, Janaina Deubatei (My University, 2024)
Toxoplasmosis is a zoonosis widely distributed around the world. The prevalence of the disease varies by region, and it is currently estimated that about two-thirds of the global population have been exposed to Toxoplasma gondii. Although most cases are asymptomatic, there are at-risk groups such as immunocompromised individuals and pregnant women. In immunocompromised individuals, the reactivation of cerebral cysts presents as the most severe complication, while in pregnant women, congenital toxoplasmosis can affect the fetus. The transmission and progression of congenital toxoplasmosis cases vary depending on the trimester of gestation during which the infection occurred, with the first trimester having the highest risk of complications and the third trimester presenting fewer damages. Adequate coverage and regular monitoring of the pregnant woman during prenatal care aim to minimize the occurrence of congenital toxoplasmosis cases. This study aimed to estimate the incidence of gestational and congenital toxoplasmosis in the municipality of Ponta Grossa (PR). It is a retrospective study based on data from the Epidemiological Surveillance of the municipality between 2014 and 2021. During this period, 724 confirmed cases of gestational toxoplasmosis were identified, of which 528 (72.83%) were diagnosed in the first trimester, 148 (20.41%) cases in the second trimester, and 48 (6.62%) cases in the third trimester. More than half (68.6%) of the seropositive pregnant women did not have a high school diploma. The average incidence of gestational toxoplasmosis in Ponta Grossa (9.7 per 1,000 pregnancies) was higher compared to the national average (3.5 per 1,000 pregnancies) and regional average (5.2 per 1,000 pregnancies). During the same period, 21 cases of congenital toxoplasmosis were confirmed, with Ponta Grossa's incidence being below the national and regional averages. During this period, two deaths due to the disease were reported. Factors influencing these indicators include the effectiveness of monitoring, lack of information, or even underreporting of cases. It is understood that the high prenatal coverage in Ponta Grossa reflects proportionally the elevated incidence when compared to national and regional averages. It may, therefore, be related to adequate monitoring and effective detection of the condition. On the other hand, the high infection rates indicate a lack of information on prophylaxis and prevention, as toxoplasmosis is associated with risk factors such as dietary habits and sanitary and environmental conditions.
Keywords: Toxoplasmose gestacional; Toxoplasmose congênita; Toxoplasma gondii; Ponta Grossa; Gestational toxoplasmosis; Congenital toxoplasmosis